Different Expression of Hypoxic and Angiogenic Factors in Human Endometriotic Lesions. (April 2016) - Filippi, Irene; Carrarelli, Patrizia; Luisi, Stefano; Batteux, Frederic; Chapron, Charles; Naldini, Antonella; Petraglia, Felice
Endometriosis is associated with local angiogenic and hypoxic mechanisms. Indeed, peritoneal fluid of women with endometriosis generates a specific microenvironment to support the growth and development of ectopic endometrial tissues. The association between proangiogenic markers and hypoxic processes in different endometriosis phenotypes was investigated in the present study, analyzing the expression of several genes, related to hypoxic signaling pathway and involved in angiogenic processes, in nonpregnant women with different forms of endometriosis. Samples of ovarian endometrioma (OMA; n = 16) or deep infiltrating endometriosis (DIE; n = 11) were collected, and in addition, control endometrium was collected from healthy women by hysteroscopy. The gene expression of the hypoxia-inducible factors (HIF) 1/2α, protease-activated receptors (PARs) ¼, and vascular endothelial growth factor (VEGF) A was evaluated by quantitative reverse-transcription polymerase chain reaction. Ovarian endometrioma expresses high levels of HIF-1/2α, PAR-1/4, and VEGF-A, while DIE did not show significantly different gene expression compared to endometrium from unaffected women. A positive correlation between the expression of HIF-1/2α and VEGF-A mRNA was observed in OMA. The overall data point out that the heterogeneity of the disease reflects differences in expression levels of genes associated with hypoxia and angiogenesis, suggesting that such conditions may have an active role in the development of the disease.